The Effects of Outdoor Activity on Patient-Reported Visual Outcomes Under Perioperative Management Using Cyclosporine and Rebamipide - Chung Min Lee; Nahee Kim; Min Young Kim; Nahyun Park; Yea Eun Lee; Jeewon Han; Hayoung Lee; Kyu Sang Eah; Yoo Young Jeon; Ho Seok Chung; Jae Yong Kim; Hun Lee (Diagnostics)
Background/Objectives: Visual recovery after cataract surgery may be affected by lifestyle and environmental factors. This study aimed to investigate the association between daily outdoor activity and patient-reported visual outcomes after cataract surgery under perioperative management using cyclosporine and rebamipide. Methods: This retrospective study included 90 eyes from patients who underwent standardized cataract surgery with implantation of TECNIS Eyhance intraocular lenses. Patients were divided into two groups based on their average daily outdoor activity during the first postoperative month: Group 1 (≤3 h/day) and Group 2 (>3 h/day). Postoperative assessments included Cataract-related Visual Function Questionnaire (CVFQ) scores, uncorrected and corrected distance visual acuity, and ocular surface parameters such as tear breakup time, Oxford score, SICCA score, and OSDI. Results: Group 1 reported significantly higher CVFQ scores for daytime (p = 0.020) and night-time driving (p = 0.037) compared to Group 2, indicating lower levels of visual discomfort in these tasks. No significant differences were observed between the groups for other CVFQ subcategories or ocular surface parameters. Conclusions: Except for driving-related discomfort, no significant differences were found in CVFQ scores between the groups. No difference in ocular surface parameters can be attributed to the perioperative management using cyclosporine and rebamipide. CVFQ may be a useful tool for assessing subjective visual outcomes after cataract surgery.